Potential involvement of the IL-33–ST2 axis in the pathogenesis of primary Sjögren's syndrome. Issue 6 (2nd January 2014) - Awada, Ahmad; Nicaise, Charles; Ena, Sabrina; Schandéné, Liliane; Rasschaert, Joanne; Popescu, Iuliana; Gangji, Valérie; Soyfoo, Muhammad S
Abstract : Objectives: To investigate the role of the interleukin (IL)-33–ST2 axis in the pathophysiology of primary Sjögren's syndrome (pSS). Methods: Serum levels of IL-33 and sST2 were determined by ELISA. The expression of IL-33 and ST2 was investigated in salivary glands (SG) by immunohistochemistry. PBMC were isolated and stimulated with IL-33, IL-12 and IL-23 and the cytokine profile response was examined by flow cytometry. Intracellular cytokine detection of IFNγ and IL-17 was performed by flow cytometry. Results: Serum IL-33 and sST2 levels were increased in pSS patients compared with controls and patients with systemic lupus erythematosus. Expression of IL-33 was upregulated in SG with Chisholm scores of 2 and 3 of pSS patients but comparable with controls for SG with Chisholm score of 4. ST2 expression in SG was downregulated in pSS patients. IL-33 at different concentrations did not increase the secretion of pro-inflammatory cytokines but acted synergistically with IL-12 and IL-23 to promote IFNγ production. NK and NKT cells were identified as main producers of IFNγ in vitro and were found in SG of pSS patients. Conclusions: IL-33 is released in pSS, and acts with IL-12 and IL-23 to favour the secretion of IFNγ by NK and NKT cells.